Preschool appropriate practices - Beaty, Janice J. (Fort Worth, TX : Harcourt Brace, 1996)
This book is about: The Self-Directed Learning Environment; The Teacher's Role; Block Center; Computer Center; Manipulative/Math Center; Book Center...
Keywords: Education; Child development; Preschool Education; Activity programs; Classroom learning centers; Education, Preschool -- Curricula; Education, Preschool -- Activity programs; Classroom learning centers; Child development